The Concept “Modesty” in the Context of British, American and Armenian Cultural Identity - Yeghiazaryan, Gayane (Armenian Folia Anglistika, 2013)
The present article provides an analysis of the concept “modesty” in the context of British, American and Armenian cultural identity. As an indicator of a common value in three linguo-cultures, the concept “modesty”, however, appears in various expressions. The article presents the similarities and differences of the value perception of the concept “modesty” in three linguo-cultures.